(untitled) (Research, Society and Development, 2022)
Medicines are considered chemical waste and a large part of the Brazilian population discards these products in sinks, vases or common waste, usually due to the lack of information on the impact of these wastes on the environment and health. This study aimed to investigate the incorrect disposal of medicines by the Brazilian population, highlighting their risks to human health and the environment, in addition to elucidating possible solutions for the correct destination and management of these chemical residues. A qualitative-quantitative and descriptive research was carried out based on books and scientific articles and legislation in Portuguese and English, in full text, published between 2012 and 2021 in the Virtual Health Library (BVS), Scientific Electronic Library database. Online (SciELO) and Pubmed. The results showed that the disposal of medicines in Brazil is a critical problem faced by both health professionals and patients. Studies have shown that reverse logistics can be a powerful tool to ensure that waste disposal is carried out by effective, safe and environmentally correct means. The safe disposal of medicines can have a significant positive impact on public health and the environment if consumers are properly educated on how to proceed accordingly.